Comparative Analysis of Palatal Depth and Nasal Septum Deviation in Patients with and without Maxillary Canine Impaction: A Cone Beam Computed Tomography Study - Shahraki, Neda; Kahnemuee, Fatemeh (Galen Medical Journal, 2024)
Background: The primary aim of this study was to compare palate depth and nasal septum deviation between patients with unilateral and bilateral buccal and palatal impactions of maxillary canines and those without impaction. Materials and Method: This cross-sectional study examined CBCT images of 60 patients from a private radiology archive, divided into four subgroups of 10 patients each with unilateral or bilateral buccal and palatal impactions, and a control group of 20 patients without impaction. Nasal deviation was assessed by measuring the distance of the maximum convexity of the deviated septum from the midsagittal plane in the coronal CBCT cut. Palate depth (PD) was measured as the perpendicular line from the middle of the axis connecting the mesiopalatal cusp of the first molar to the hard palate. Measurements were performed using NNT 16.3.1 software and validated by radiology and orthodontics specialists. Independent t-tests were used for statistical comparisons. Results: There were no significant differences in palate depth (p > 0.05) or nasal septum deviation (p > 0.05) between the control group and patients with unilateral or bilateral buccal and palatal impactions of maxillary canines. Conclusion: The study found no significant differences in palate depth and nasal septum deviation between patients with and without maxillary canine impaction, suggesting that impaction does not significantly affect these anatomical features. Further research is recommended to explore these findings in larger populations.